Effect of Oat Bran Incorporation on the Physicochemical and Sensory Properties of Tempeh Crisp (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Tempeh, a fermented soybean product, is known as a cost-effective, protein-rich, and health-promoting food. Tempeh crisp, a preserved version of tempeh, extends its shelf life by removing moisture and halting fermentation. However, this product's low fibre content and the limited research on its characteristics and acceptability limit its commercialization. Oat bran, a byproduct of oats rich in dietary fibre, vitamins, and minerals, offers the potential to enhance the tempeh crisp’s nutritional profile. This study investigates the effects of incorporating oat bran (OB) on the physicochemical properties and sensory attributes of tempeh crisps. Tempeh crisp was prepared with varying ratios of oat bran and tapioca flour (TF): Control A (0% OB: 100% TF), B (10% OB: 90% TF), C (20% OB: 80% TF), and D (30% OB: 70% TF). Proximate analysis revealed significant differences (p
Keywords: Fermented product; Legume; Byproduct; Dietary fibre; Healthy snacks